Collective remembering: new developments and future perspectives - (:unkn) unknown (Culture & Psychology: Sage, 2017)
From discussions in the media about this year’s 70th anniversary of the end of the Second World War to debates about the content of school history textbooks, collective memory is a topic that permeates public and scientific forums alike. What we remember and, most importantly, how we remember the past, seems fundamental for the way in which we come to understand our present and imagine our future as individual, groups, and societies (Liu & Hilton, 2005). And yet, the debate concerns not only the content of collective memory but the concept of collective memory itself, its definition, applicability, and its future (Brockmeier, 2010). Collective remembering can be broadly defined as the process by which discourses on the historical past are produced. Beyond the questions of ‘who’ does the remembering, ‘how’, and ‘for what purposes’, this broad understanding might sound like a solid starting point for this research area. However, it is not so much shared definitions that unify the field, but rather a critique of old approaches to collective memory, accused of turning it into static, reified representations about the past (Wertsch, 2002). Beyond this critique, important questions remain concerning the content of collective memory (is it a narrative, a form of meaning-making, a representation?), its functions (is it a way to define ourselves, to give meaning to the world, to imagine what may come next?), and its boundaries (does it concern only recent events, only the past of one’s social group, or does it refer to a global understanding of history?). Answers to such questions tend to vary from researcher to researcher. However, they are not always contradictory and could actually complement each other. This makes dialogue between scholars all the more important for understanding and articulating the different aspects of collective memory. In addition, there is also value in looking ‘outwards’ for inspiration, beyond the area of collective memory. Plagued by a narrow definition of memory in psychology (as recall), the field of collective memory tends to operate with a broader understanding of what remembering is. From a sociocultural perspective, to remember involves much more than memory alone (Wagoner, 2015) and engages one’s imagination and creativity in a complex act of future-making. As such, it becomes important to have an inter-disciplinary dialogue between collective memory scholars and colleagues working in related fields within social and cultural psychology. This special issue aims to bring together a small group of junior and senior researchers who share both a common interest for collective remembering and connected topics, as well as a set of theoretical assumptions about the social and cultural nature of human activity and the future-oriented nature of constructing meaning about self and world. Its primary aim is to open up a space for discussion between cultural psychologists interested in how discourses on history are used and produced and for their theoretical and practical consequences.
Keywords: collective memory; cultural psychology